Effects of Miglitol on Caloric Efficiency and Lipid Profiles in Obese Male SHR/Ntul//-cp Rats - Tulp, Orien L (British Journal of Healthcare and Medical Research, 2024)
Elevations in plasma lipid profiles are a common observation in overweight, obese, hyperinsulinemic, and adult-onset diabetes. The effects of luminal inhibition of starch digestion on parameters of weight gain and plasma lipid profiles were determined in groups of adult obese male T2DM SHR/Ntul//-cp rats. Animals were fed a USDA-formulated, nutritionally complete diet containing 54% sucrose (SUC, CHO) component (Control) or the same diet containing a pharmacologic α-glucosidase inhibitor (1,5 dideoxy-1,5-[(2-hydroxyethyl) imino]-D glucitol; generic miglitol), 150 mg/kg diet, ad libitum for up to 8 weeks. Miglitol resulted in modest decreases in food intake and net weight gain. At the end of the study. heparinized bloods were collected for determination of plasma cholesterol, low-density lipoprotein (LDL) and high density lipoprotein (HDL) fractions. The miglitol-associated luminal inhibition of glucosidase activity resulted in 20% reduction in total cholesterol, and in both α- (LDL) and β-lipoprotein (HDL) fractions. These results indicate that simple inhibition of luminal α-glucosidase activity via miglitol may be a useful adjunct in the clinical management of hypercholesterolemia in states of obesity, T2DM and other glucose intolerant states, in addition to therapeutic applications in enhancing and improving glycemic control in man and animals.